Optimal Design of Grid Connected Photovoltaic System at UTHM using HOMER Software - Abdullah, Mohd Noor; Mat Rahim, Muslim (Evolution in Electrical and Electronic Engineering, 2022)
TThis paper presents an optimal grid-connected photovoltaic (GCPV) system design at the UTHM by using HOMER Software. The main purpose of this project is to reduce UTHM’s annual energy usage and electricity bill. Based on the UTHM campus energy usage and electricity bill data reveal that the monthly utilization of electricity on the UTHM campus is very high and costly. Besides that, to reduce CO2 emissions emitted from producing electricity. Therefore, this paper proposed the development of a GCPV system for the G3 Block building, Perpustakaan Tunku Tun Aminah (PTTA) building and Fakulti Kejuruteraan Awam and Alam Sekitar (FKAAS) based on Monocrystalline PV modules. The total proposed of GCPV system capacity can be installed up to 4351.17 kW and simulated using HOMER software. The simulation results show that the grid-connected PV system can significantly reduce the UTHM campus annual operating cost by 10% per year, UTHM campus annual grid purchase cost by 10.3% per year, UTHM campus Average Grid Purchase kWh by 11.5% per year and the carbon dioxide emission by 10.3% per year. As a result, the proposed GCPV system at the UTHM campus can be reduced up to RM 2,263,651 per year.